2013
DOI: 10.1186/1476-511x-12-89
|View full text |Cite
|
Sign up to set email alerts
|

High levels of anti-inflammatory and pro-resolving lipid mediators lipoxins and resolvins and declining docosahexaenoic acid levels in human milk during the first month of lactation

Abstract: BackgroundThe fatty acid mixture of human milk is ideal for the newborn but little is known about its composition in the first few weeks of lactation. Of special interest are the levels of long-chain PUFAs (LCPUFAs), since these are essential for the newborn’s development. Additionally, the LCPUFAs arachidonic acid (AA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are precursors for lipid mediators which regulate inflammation.MethodsWe determined the composition of 94 human milk samples from 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 87 publications
6
106
0
Order By: Relevance
“…The amounts of SPMs detected in this study would equate to low-mid nanomolar tissue concentrations, which are biologically significant. SPMs and their precursors have also previously been detected in normal human plasma and lymphoid organs (Mas et al 2012, Markworth et al 2013, Colas et al 2014 and in human milk (Weiss et al 2013). Similar to our studies, markedly higher concentrations of the primary Rv precursors, 17-HDHA and 18-HEPE, were detected in these studies compared with their downstream products.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The amounts of SPMs detected in this study would equate to low-mid nanomolar tissue concentrations, which are biologically significant. SPMs and their precursors have also previously been detected in normal human plasma and lymphoid organs (Mas et al 2012, Markworth et al 2013, Colas et al 2014 and in human milk (Weiss et al 2013). Similar to our studies, markedly higher concentrations of the primary Rv precursors, 17-HDHA and 18-HEPE, were detected in these studies compared with their downstream products.…”
Section: Discussionsupporting
confidence: 79%
“…Circulating SPMs have been measured in healthy subjects (Mas et al 2012), with concentrations shown to be associated with n-3 PUFA intake (Colas et al 2014) and produced in greater amounts after exercise in patients taking ibuprofen (Markworth et al 2013). SPMs have been measured in breast milk (Weiss et al 2013), but to date have not been investigated in the context of human pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…PE-labeled anti-human CD80 Ab, allophycocyanin-labeled anti-human CD206 Ab, and the IgG1K isotype control were purchased from R&D Systems. RvD1 (7S,8R,17S-trihydroxy-4Z,9E,11E,13Z,15E,19Z-docosahexaenoic acid) produced by stereospecific total synthesis (23) was purchased from Cayman Chemicals (Ann Arbor, MI) and was verified by liquid chromatography-mass spectrometry/ mass spectrometry analysis in the laboratory (24).…”
Section: Methodsmentioning
confidence: 99%
“…Chemerin Receptor 23, anti-human, mAb (ChemR23 Ab) and isotype IgG3, PE-labeled anti-human CD80, monoclonal allophycocyanin-labeled anti-human CD206 Ab, and the IgG1K isotype control were purchased from R&D Systems Europe. RvE1 (5S,12R,18R-trihydroxy-6Z,8E,10E,14Z,16E-eicosapentaenoic acid) produced by stereospecific total synthesis (14) was purchased from Cayman Chemicals (Ann Arbor, MI) and was verified by liquid chromatography-tandem mass spectrometry analysis in the laboratory (29).…”
Section: Methodsmentioning
confidence: 99%